Удосконалення методів та розроблення віртуального засобу оцінювання якості продукції овочівництва - Мідик, Ігор-Михайло Володимирович (Національний університет "Львівська політехніка", 2021)
Проаналізовано методи аналізу якісного та кількісного складу харчових продуктів. На основі проведеного огляду методів контролю якості овочів визначено, що перспективним методом кількісного аналізу вмісту мінеральних речовин в овочах є кондуктометричний метод дослідження рідин, що ґрунтується на вимірюванні електричної провідності. На основі математичного аналізу з використаннямтеорії нечітких множин вивчено вплив мінеральних добрив на вміст корисних речовин (клітковини, вуглеводів, білків). При цьому, задача розв’язана у три етапи: 1) апроксимація результатів впливу мінеральних добрив на вміст корисних речовин 2) симплекс – метод. Знаходження оптимальних значень задачі лінійного програмування - параметрів w0 та d0 3) розв’язок системи нерівностей із шуканим результатом – марка мінеральних добрив. Також здійснений розрахунок функції належності цілі та обмежень для повної картини розв’язку математичної задачі. Досліджено можливості відомого імітансного методу для контролю показників якості овочевого соку. У кондуктометричну комірку поміщались модельні рідини – овочеві соки з домішками важких металів. Вивчено залежності активної та реактивної складових електропровідності овочевого соку з домішками іонів міді та натрію в частотному діапазоні 50 Гц - 100 кГц. Використання отриманих залежностей покращує інформативність електричних досліджень і, таким чином, підвищує оперативність аналізу показників якості. Розроблений засіб вимірювання та отримані залежності дають змогу здійснювати експрес-контроль вмісту домішок в овочевих соках за електричними параметрами. Для імітансного контролю показників якості овочевого соку запропоновано і реалізовано віртуальний засіб вимірювання на основі апаратно-програмної платформи LabVIEW та з блоком NI USB 6009. Віртуальний прилад у складі: ПК з програмним забезпеченням LabVIEW, згаданого блоку NI USB 6009 та кондуктометричної комірки з соком вжито для визначення вмісту важких металів у цьому соці. Тим самим, доведено, що у виробничих умовах при незначних витратах можна оперативно контролювати якість овочів, з яких отримують досліджуваний сік. Проанализированы методы анализа качественного и количественного состава пищевых продуктов. На основе обзора методов контроля качества овощей определено, что перспективным методом количественного анализа содержания минеральных веществ в овощах есть кондуктометрический метод исследования жидкостей, основанный на измерении электрической проводимости. На основе математического анализа с использованием теории нечетких множеств изучено влияние минеральных удобрений на содержание полезных веществ (клетчатки, углеводов, белков). При этом, задача решена в три этапа: 1) аппроксимация результатов воздействия минеральных удобрений на содержание полезных веществ 2) симплекс - метод. Нахождение оптимальних значений задачи линейного програмирования - параметров w0 и d0 3) решение системы неравенств с искомым результатом - марка минеральных удобрений Расчет функции принадлежности цели и ограничений для полной картины решения математической задачи. Исследованы возможности известного имитансного метода для контроля показателей качества овощного сока. Для экспериментальных исследований разработана структура измерительного средства в составе кондуктометрической ячейки, RLС-метра, блоков управления и обработки результатов. В кондуктометрическую ячейку помещались модельные жидкости - овощные соки с примесями тяжелых металлов. Изучены зависимости активной и реактивной составляющих электропроводности овощного сока с примесями ионов меди и натрия в частотном диапазоне 50 Гц - 100 кГц. Использование полученных зависимостей улучшает информативность электрических исследований и, таким образом, повышает оперативность анализа показателей качества. Разработан способ измерения и полученные зависимости позволяют осуществлять экспресс-контроль содержания примесей в овощных соках по электрическим параметрам. Для иммитансного контроля показателей качества овощного сока предложено и реализовано виртуальное средство измерения на основе аппаратно-программной платформы LabVIEW с блоком NI USB 6009. Виртуальный прибор в составе ПК с программным обеспечением LabVIEW, упомянутого блока NI USB 6009 и кондуктометрической ячейки с соком приняты для определения содержания тяжелых металлов в этом соке. Тем самым, доказано, что в производственных условиях при незначительных затратах можно оперативно контролировать качество овощей, из которых получают исследуемый сок. The dissertation is devoted to the improvement of methodological and metrological assurance of quality control of vegetables and juices from them on the basis of their electro physical parameters analysis with the help of virtual means of immitance control. The first section analyzes the methods for the qualitative and quantitative composition of food products. Measuring methods of analysis are based on the physical, chemical and biological properties of the substance. The described methods are briefly described; their advantages and disadvantages are indicated. Electrochemical methods, which are related to changes in structure, chemical composition and concentration, are shown to be effective and provide qualitative and quantitative analysis of substances in gas, liquid or solid state. Informative parameters, in this case, are electrical parameters. In the second section, a comparative analysis of the normative base of Ukraine was carried out in order to approximate the legislation on quality and safety of vegetables and their products to the standards of international law. To optimize the overall quality index, it is proposed to use the mathematical apparatus of the theory of fuzzy sets, since the characteristics of the product must be in a certain range. As a result, several mathematical models for the complex evaluation of the quality of agricultural products for fuzzy constraints are constructed: I model is a model for identifying vegetables with the highest content of fiber, carbohydrates and proteins, depending on the amount of mineral fertilizers (maximum value of the function defining a complex quality index); II Model - a model for achieving the maximum weight of agricultural products (maximum value of the function of mass depending on mineral fertilizers); III model - a model for ensuring the cultivation of agricultural products with specified parameters of the proportion of nutrients (carbohydrates, proteins); IV Model is a model of safety of vegetables, that is, a model for assessing the safety of products in relation to its contamination by heavy metals. Based on mathematical analysis using fuzzy set theory, the effect of mineral fertilizers on the content of nutrients (fiber, carbohydrates, proteins) has been studied. In this case, the problem is solved in three stages: 1) Approximation of the results of the influence of mineral fertilizers on the content of nutrients 2) Simplex - method. Finding the parameters w0 and d0 3) The solution of the system of inequalities with all the desired results - the brand of mineral fertilizers, mathematical parameters λ Calculation of the goal affiliation function and constraints for a complete picture of the solution of a mathematical problem. In the third section, a processing of the results was developed. In conductivity cell was placed model liquids - vegetable juices with impurities of heavy metals. The dependences of the active and reactive components of electrical conductivity of vegetable juice with impurities of copper ions and sodium ions on the frequency of the electromagnetic field of 50Hz-100kHz were studied. It was found on the basis of experimental study: 1) As the frequency of the test signal increases, the active component becomes constant (independent of frequency), and the reactive component approaches zero. As the purpose of research is complex conductivity, I consider research on high frequencies uninformative. 2) At frequencies below 1000 Hz, the experimentally obtained inverse dependence of the active and reactive components of conductivity, which provides information on the quality of juice without additives. 3) In the presence of heavy metal impurities in the controlled juice sample, using immittance measurements, it is possible to prove the efficiency of this method for qualitative and quantitative analysis of carrot juice. The fourth chapter presents a developed virtual means for measuring the imitation of vegetable juice was described. For immitance control of vegetable juice quality indicators, a virtual measuring device based on the LabVIEW hardware platform and a compatible NI USB 6009 unit was proposed and implemented. This enabled the rapid analysis of the juice content of the mineral substances by electrical parameters. Thus, in production conditions, at a negligible cost, you can quickly control the quality of vegetables from which the juice is obtained. The virtual device consists of: a PC with LabVIEW software, the mentioned NI USB 6009 block and a conductivity cell with juice used to determine the content of heavy metals in this juice. To measure and calculate the imitation of the object, a sinusoidal test signal was generated in the form of voltage variable amplitude of 10-20 mV. Since the NI USB 6009 unit is not capable of generating alternating voltage, the program uses certain elements of the NI-DAQ task with the While Loop with Stop Button cycle. To do this, it was created the Channel Generation - Create Channel (Start Task, Write, Clean Task), and Wait, which governs the sinusoidal period. The immittance values were obtained by mathematical processing of voltage and current signals of the conductometric cell with the investigated juice. The operation of mathematical processing is provided by the algorithm of the virtual measuring instrument. It was carried out in three possible ways: 1. The classical method, which involves the use of Euler's equation. 2. A method of measuring active and reactive power and dividing the effective value of the signal power by the square of the current value. 3. Method using exponential Fourier transformation using the voltage and current signals of the measured object to estimate the first harmonics.
Совершенствование методов и разработка виртуального средства оценки качества продукции овощеводства
Improvement of methods and design of a virtual mean of vegetable products quality assessment
Keywords: електропровідність; імітанс; адмітанс; кондуктометрична комірка; ємнісний перетворювач; модельна рідина; моделювання; активна складова адмітансу; реактивна складова адмітансу; нечіткі множини; віртуальний засіб вимірювання; апаратно-програмна платформа LabVIEW; блок NI USB 6009; NI-DAQ задача; державний стандарт; міжнародні стандарти; электропроводность; иммитанс; адмиттанс; кондуктометрическая ячейка; емкостный преобразователь; модельная жидкость; моделирование; активная составляющая адмиттансу; реактивная составляющая адмиттансу; нечеткие множества; виртуальное средство измерения; аппаратно-программная платформа LabVIEW; блок NI USB 6009; NI-DAQ задача; государственный стандарт; международные стандарты; electrical conductivity; immittance; admittance; conductivity meter; capacitance converter; model fluid; modeling; active component of admittance; reactive component of admittance; fuzzy sets; virtual measuring instrument; LabVIEW hardware platform; block NI USB 6009; NI-DAQ task; state standard; international standards; 006;004.9;60;620